Municipal Waste Characterization and Reduction Potential in Singaraja City - Anak Agung Mas Untari; I Made Wahyu Wijaya; I GD Yudha Partama; Kailas Deoram Ahire (Jurnal Ilmu Lingkungan, 2024)
The Bengkala Landfill serves as the sole waste disposal site in the Buleleng Regency, and its current waste accumulation has exceeded the landfill's capacity. The local government has endeavoured to reduce the influx of waste to the landfill by establishing a Recycling Centre (RC) for waste processing. This research aims to analyse the generation and characteristics of waste in Singaraja City, as well as its recycling potential, to support RC planning. The study's method is to look at how much waste is made and what kinds of things are made from it by using measurements made by the local government of Buleleng Regency in line with the Indonesian National Standard (SNI) 19-3964-1994. The analysis reveals that Singaraja City produces approximately 606.23 kg/day of waste, with a density of 0.244 kg/L. Organic waste dominates, constituting 66.31% of the total waste composition. Food waste and foliage are the highest components of organic waste, underscoring the significance of food waste reduction, including composting. Paper, wood, and plastic contribute 8.23%, 1.41%, and 14.57% of the waste, respectively. The study of waste composition in Singaraja City reveals both opportunities and challenges in waste management and sustainability. Singaraja City can benefit from initiatives such as plastic reduction programmes, glass recycling, and hazardous waste management to achieve sustainable waste practices. Achieving these goals necessitates public education, policy interventions, recycling infrastructure development, and stakeholder collaboration.